STRES KERJA, MOTIVASI KERJA, DENGAN DUKUNGAN SOSIAL SEBAGAI VARIABEL MODERATOR - IMROATIN (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: Healthy condition,a calm mind without any interruption in work stress will bring employees feel comfortable in working. Some companies prepare employees to deal with any problems that arise in order to increase company productivity and meet the expected target, especially companies moving area in the manufacturing of PT Apie Indo Karunia. This research is causality work stress as the independent variable, the dependent variable that work motivation and the moderator variable social support. The technique of sampling using probability sampling with simple random sampling with a sample of 51 full-time employees production department PTApie Indo Karunia, Sidoarjo.The analytical method used was Partial Least Square with the help of Smart PLS software. The results showed that the stress of work and a significant negative effect on work motivation, and social support and a significant positive effect, namely that social support is able to moderate the stress of working on work motivation. Keywords :work stress, work motivation, and social support.